PENGARUH KOMPETENSI, SELF EFFICACY DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR BIRO UMUM DAN PROTOKOL SETDA PROVINSI BALI - Desak Nyoman Indriyani; I Nengah Suardhika; Putu Agus Eka Rismawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Performance is the result of work that can be achieved by a person or group of people in an organization, in accordance with their respective authorities and responsibilities, in an effort to achieve the goals of the organization concerned legally, not violating the law and in accordance with morals and ethics. Performance can be seen how a person at work carries out his duties properly, which is supported by the ability, expertise, independence, commitment, responsibility and individual confidence in carrying out his work. Performance is an important thing that must be achieved by every company, including the General Bureau Office and Regional Secretariat Protocol Office of Bali Province, and the factors that influence performance include competence, self-efficacy and work environment. This research was conducted at the Office of the General Secretariat and Protocol Bureau of Bali Province. The number of samples taken was 100 people. Data collection was carried out through a questionnaire. The analysis technique used is multiple linear regression. Which is processed using the SPSS program version 21.0 for windows. Based on the results of the analysis, this study shows that competence has a positive and significant effect on employee performance, which means that if employee competencies are owned and used properly, performance at the Office of the General Bureau and Regional Secretariat Protocol of the Province of Bali will increase. Self efficacy has a positive and significant effect on employee performance, which means that if employee self-efficacy increases, the self-confidence of the performance of the General Bureau and Protocol Regional Secretariat of the Province of Bali. The work environment has no significant effect on performance, which means that if a good environment does not necessarily improve the performance of employees at the Office of the General Affairs Bureau and the Regional Secretariat Protocol, Bali Province.